Regenerative responses of rabbit corneal endothelial cells to stimulation by fibroblast growth factor 1 (FGF1) derivatives, TTHX1001 and TTHX1114. (28th February 2022) - Weant, Jessica; Eveleth, David D.; Subramaniam, Amuthakannan; Jenkins-Eveleth, Jennifer; Blaber, Michael; Li, Ling; Ornitz, David M.; Alimardanov, Asaf; Broadt, Trevor; Dong, Hui; Vyas, Vinay; Yang, Xiaoyi; et al.
Abstract: Utilising rabbit corneal endothelial cells (CEC) in three different paradigms, two human FGF1 derivatives (TTHX1001 and TTHX1114), engineered to exhibit greater stability, were tested as proliferative agents. Primary CECs and mouse NIH 3T3 cells treated with the two FGF1 derivatives showed equivalent EC50 ranges (3.3–24 vs.1.9–16. ng/mL) and, in organ culture, chemically lesioned corneas regained half of the lost endothelial layer in three days after treatment with the FGF1 derivatives as compared to controls. In vivo, following cryolesioning, the CEC monolayer, as judged by specular microscopy, regenerated 10–11 days faster when treated with TTHX1001. Over two weeks, all treated eyes showed clearing of opacity about twice that of untreated controls. In all three rabbit models, both FGF1 derivatives were effective in inducing CEC proliferation over control conditions, supporting the prediction that these stabilised FGF1 derivatives can potentially regenerate corneal endothelial deficits in humans.